Hambatan dalam Proses Eksekusi Putusan terhadap Pemeliharaan Anak dalam Perkara Perceraian di Pengadilan Agama - Retno Wulansari (UIN Sunan Kalijaga Yogyakarta, 2015)
This research aims to know about how the impediment that occurs in executionof the award against child maintenance in the matter of divorces in the religious courtand how the efforts taken to complete the obstacles in execution of the award againstchild maintenance in the matter of divorces in the religious court. The research isjuridical law normative research which research materials that looked at law such aslegislation, basis, the doctrine and other legal document. This research produce theconclusion that the impediments that obstruct execution of the award on childmaintenance in the matter of divorces in the religious court can divided into two namelyobstacles that are juridical as the absence of rules that is special and detail concerningthe execution of this type of and opposition parties termohon execution. Obstacles whichare non juridical is execution device is not ready yet and the object execution was the sonof as living creatures. Efforts to be performed in completing these constraints amongother increase professionalism of law enforcement, discovery of the law, used the aid of amediator and chairman of the court and execution devices must understand aboutproblems given for this dispute and conditions that occurred in the field.